Analisis Stabilitas Hasil pada Pengujian Kultivar Tebui. (Yield Stability Analysis on Sugarcane Cultivars Trial). - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1984)
Among methods for estimating yield stability measurement proposed by several authors,_ Finlay and Wilkinson model (1963) and Eberhart and Russel model (1966) were the most frequently used. Yield stability analysis based on mean yield, and regression coefficient as proposed by Finlay and Wilkinson was less precise. One additional parameter i.e. variance of deviation from regression as proposed by Eberhart and Russel will improve the conclusions. This fact was encountered in the analysis of multilocation test of six sugarcane cultivars developed by the Sugarcane Estate Research Institute at Pasuruan, and two introduced cultivars from Fiji and Hawaii at 27 Locations distributed in Java, in the 1975/1976 planting season. . â¢ The result of this test indicated that PS 41, PS 46, PS 47 and PS 48 (Finlay & Wilkinson method) and ps 41, PS 47, and P5 48 (Eberhart & Russel method) were the most stable and out-yielding cultivars.